The Precariousness of Situation: Introduction to the Dossier Situated Studies on Another Literatures (El Taco en la Brea, 2023)
This is the introduction to the dossier Situated Studies on Other Literatures, in which the categories of other literature and situated knowledge are reconceptualised.
Keywords: situated studies; Aby Warburg; post‒comparatism; precariousness; readings